Complete mitochondrial genome of Oberea diversipes (Coleoptera, Cerambycidae) - Tian, Lichao (Mitochondrial DNA B Resour, 2020)
The complete mitochondrial DNA genome of the Oberea diversipes was reported. The genome was a circular molecule of 15,499 base pairs (bp), with 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and an estimated 830 bp A + T-rich control region. The total base composition of the mitogenome was A–T bias, with 40.9% for A, 37.0% for T, 13.4% for C, and 8.7% for G. The molecular data presented here would be useful for further study of O. diversipes.